2020
DOI: 10.3389/fimmu.2020.563622
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: PD-1 Inhibitor Is Active in Lung Adenocarcinoma With B Cell Deficiency

Abstract: Introduction: In murine cancer models, B cells are unnecessary for efficacy of PD-1 inhibitor. However, we do not know whether this applies to clinical settings, especially in patients with non-small-cell lung carcinoma (NSCLC). Case presentation: We report on the case of an advanced lung adenocarcinoma patient without oncogenic driver mutations whose disease progressed on second-line bevacizumab-containing chemotherapy regimens. These previous treatments resulted in profound thrombocytopenia and increased num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…To date, only a few cases of advanced lung cancer with B-cell lymphoma have been reported. Two of these cases were successfully treated with alectinib or osimertinib ( 10 , 11 ) whereas the other cases reported partial efficacy of sintilimab treatment and exacerbation after pembrolizumab treatment in patients with advanced lung cancer and B-cell lymphoma ( 2 ) To the best of our knowledge, this is the first report of pembrolizumab treatment following one course of BR therapy for advanced NSCLC accompanied by MALT lymphoma, which resulted in good disease control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, only a few cases of advanced lung cancer with B-cell lymphoma have been reported. Two of these cases were successfully treated with alectinib or osimertinib ( 10 , 11 ) whereas the other cases reported partial efficacy of sintilimab treatment and exacerbation after pembrolizumab treatment in patients with advanced lung cancer and B-cell lymphoma ( 2 ) To the best of our knowledge, this is the first report of pembrolizumab treatment following one course of BR therapy for advanced NSCLC accompanied by MALT lymphoma, which resulted in good disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Three reports have investigated the treatment of B-cell lymphoma complicated with other solid cancers with ICIs ( Table I ). Two studies reported that MALT lymphoma with solid tumors was controlled by ICI treatment followed by rituximab monotherapy or rituximab-included chemotherapy ( 2 , 9 ) and one of which achieved CR for MALT lymphoma and PR for lung cancer by treatment with five courses of rituximab-included regimen, followed by sintilimab monotherapy ( 2 ). Another study reported CR for MALT lymphoma that developed during pembrolizumab treatment for urothelial cell carcinoma and was treated with four courses of rituximab ( 9 ) These cases suggest that ICIs with rituximab-containing regimens may be effective in these populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative way to study the role of the humoral pathway would be to evaluate ICI in different types of B-cell deficiency. For example, it was demonstrated in murine studies (with B-cell depleting antibodies or strains lacking mature B-cells) that the presence of B-cells is not required for a tumour response to anti-PD-1 therapy [ 40 ]. In a patient with hypogammaglobulinemia after rituximab treatment (for marginal zone B-cell lymphoma), a partial response of the PD-1 inhibitor sintilimab was observed in advanced lung adenocarcinoma (co-existing in the same patient) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%